انتشار قصور الدرق عند الأطفال المراجعين لعيادة الغدد الصم بشكوى قصر القامة في مستشفى تشرين الجامعي - شريتح أحمد; حيدر أحمد; فرحات هناء (Latakia University Journal -Medical Sciences Series, 2019)
أهمية وهدف البحث: يعتبر قصر القامة مشكلة صحة عامة بسبب آثاره النفسية والاجتماعية والقلق الذي يثيره عند الأهل والطفل معا،وأحد أهم الأسباب الغدية له هي قصور الغدة الدرقية. تم إجراء هذه الدراسة لتحديد انتشار قصور الدرق عند الأطفال قصار القامة. طرق البحث: تم إجراء دراسة مقطعية وصفية مستعرضة على 150 طفلاً قصير القامة ، بعمر 3-14 سنة من المراجعين لعيادة أمراض الغدد الصم في مستشفى تشرين الجامعي في اللاذقية في عامي 2017-2018. تم إجراء معايرة ل TSH , FT4 . النتائج: بلغت نسبة قصور الدرق 18,7% عند الجمهرة المدروسة و مثلت الشريحة العمرية ( 3-9 (سنة النسبة الأكبر حوالي (70%)من مجمل مرضى قصور الدرق. ظهر قصور الدرق تحت السريري بنسبة 55% من حالات قصور الدرق وبمعدل حدوث أعلى عند الذكور . وجد فارق ذو قيمة احصائية بالنسبة لأطوال الأطفال المصابين بقصور الدرق وغير المصابين حيث كان الانحراف المعياري أقل عند الأطفال المصابين بقصور الدرق. P-Value :0,04 وكان الفارق ذو قيمة احصائية هامة جدا بالنسبة لأطوال الاطفال المصابين بقصور الدرق حيث كان الانحراف المعياري أقل عند الأطفال المصابين بالشكل السريري. P-Value: 0,006 وكذلك فارق ذو قيمة احصائية هامة بالنسبة لأوزان الأطفال المصابين بقصور الدرق وغير المصابين حيث كان الانحراف المعياري أقل عند الأطفال غير المصابين .P-Value:0,03 الاستنتاجات: تُظهر الدراسة الانتشارالهام لقصور الدرق المكتسب عند الأطفال قصار القامة وأهمية معايرة TSH ضمن الاستقصاءات الأولية لتحري سبب قصر القامة وذلك إما لوضع تشخيص قصورالغدة الدرقية أو نفيه والبدء باستقصاءات غدّية أخرى حيث لايمكن إجراء تحريض لهرمون النمو إلا بعد التأكد من سلامة الوظيفة الدرقية. Objective: Short stature is a public health problem because of its psychological and social effects and the anxiety which it raises in the parents and the child together, and one of the most important endocrine causes of short stature is hypothyroidism. The aim of this study is to determine the prevalence of hypothyroidism in children with short stature.. Methods: An observational descriptive cross-sectional study on 150 children with short stature aged 3-14 years undertaken at the outpatient pediatric endocrine clinic of the Tishreen University Hospital in Lattakia between" 2017-2018. TSH and FT4 was calibrated. Results: The prevalence of hypothyroidism was 18.7% among the studied population. The age group (3-9) was the largest percentage (about 70%) of all patients with hypothyroidism.. subclinical hypothyroidism was 55% of cases of hypothyroidism and a higher incidence of male. A statistically significant difference was found for the lengths of children with hypothyroidism and the other patients where was the standard deviation lower in children with hypothyroidism. (P-Value: 0.04) .We also found a significant statistical difference for the lengths of children with hypothyroidism where the standard deviation was lower in children with clinical form ( P-Value: 0.006) We found for the weights a statistically significant difference in children with hypothyroidism and other patients where was the standard deviation lower in the the rest of the studied children. (P-Value: 0.03) Conclusions: The study shows the prevalence of hypothyroidism in children with short stature and the importance of TSH calibration in preliminary investigations to determine the cause of short stature, either to diagnosis hypothyroidism or to exile it and to initiate other endocrine investigations where growth hormone induction can only be performed with normal thyroid function.